Inhibition of cancer cells using target-specific 2A3 antibody-conjugated gold nanoclusters - Jui-Chi Kuo; Tsung-Rong Kuo; Fajar Rinawati; Erna Susilowati; Sucipto; Dyah Ika Krisnawati (Acta Biochimica Indonesiana, 2021)
Background: Metal nanoclusters (NCs) with outstanding structural and optical properties have been intensively validated for applications in nanomedicine and nanotechnology. Carcinoembryonic antigen-related cell adhesion molecule 6 (CEACAM6) is overexpressed in many cancer cells. Objective: The gold nanoclusters conjugated with a single domain antibody targeting CEACAM6 of 2A3 (2A3-AuNCs) were synthesized for the inhibition of cancer cells. Methods: 2A3-AuNCs were prepared via a facile hydrothermal approach. The cell viability was measured by resazurin dye reduction assay. The cell death was analyzed by fluorescence imaging. Results: Structural and optical characterizations demonstrated the successful synthesis of 2A3-AuNCs with a roughly spherical shape and a size of 2.35 nm. The 2A3-AuNCs revealed a maximum fluorescence intensity at 350 nm with a fluorescence quantum yield of 4.0%. The cell viability assay indicated that 2A3-AuNCs could inhibit the growths of cancer cells with overexpressed CEACAM6, including breast cancer MDA-MB-231 and MDA-MB-468 cells. The fluorescence imaging results also demonstrated that 2A3-AuNCs could inhibit the growth of cancer cells with MDA-MB-231 and MDA-MB-468 cells. Conclusion: Combination with the results of cell viability assay and fluorescence imaging, the surface ligand of 2A3 antibody on 2A3-AuNCs exhibited promising inhibition of CEACAM6 overexpressed cancer cells. Our work provides a potential application of AuNCs in cancer therapy.